On some new seminormed sequence spaces defined by modulus functions - Altin, Yavuz; Işik, Mahmut (My University, 2006)
In this paper we introduce the sequence spaces l?(f, p, ?, q, s), c0(f, p, ?, q, s) and c(f, p, ?, q, s) using a modulus function f and defined over a seminormed space (X, q), seminormed by q. We study some properties of these sequence spaces and obtain some inclusion relations. © 2006 by the University of Notre Dame. All rights reserved.
Keywords: Invariant mean; Modulus function; Seminorm